Herbal Medicine in Gynecological and Obstetric Care: A Comprehensive Review of Clinical Trials - Khormi, Ali Hassan (Indian Journal of Pharmaceutical Education and Research)
This review comprehensively evaluates clinical trials assessing the efficacy and safety of herbal medicines and natural products in managing gynecological and obstetric conditions. With increasing interest in complementary and alternative medicine, herbal treatments for premenstrual syndrome, dysmenorrhea, menopause, postpartum recovery, and infertility were examined. Key herbs include Vitex agnus-castus for PMS, Zingiber officinale for dysmenorrhea, Hypericum perforatum for postpartum depression, and Crocus sativus for mood regulation. Herbal preparations were also assessed for their role in enhancing lactation, preventing postpartum hemorrhage, and improving fertility. Safety, potential side effects, and interactions were critically analyzed. A methodological appraisal of clinical trials highlights challenges and future research directions. This review provides evidence-based insights for healthcare professionals, researchers, and policymakers, supporting the integration of herbal medicine into women’s healthcare.
Keywords: Clinical Trials; Gynecological Ailments; Herbal Medicine; Natural Products; Obstetric Health